Analisis dan Optimalisasi Cycle Time Inbound Barang dengan Time and Motion Study - Munthe, Marcell Fernando N; Ariyanny, Enny (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the analysis and optimization of inbound process cycle time in the warehouse of PT DSV Solutions Indonesia using the Time and Motion Study method. The primary objective is to identify activities that serve as bottlenecks and to establish standard times for key processes, including unloading, sorting, labeling, and Goods Receipt. The analysis reveals that labeling is the main bottleneck, with the highest standard time, significantly impacting overall inbound cycle efficiency. Performance comparison between shifts indicates that Shift B is more efficient and stable than Shift A. The study provides improvement recommendations and time management strategies to enhance warehouse operational effectiveness. The findings contribute to the development of precise work time measurement methods and best practices in logistics management within warehouse industry.